Calibration process for diagnosing dental caries using the DMFT index = Proceso de calibración para el diagnóstico de caries dental utilizando el índice CPO - Garcés Elías, María Claudia
The DMFT index is an optimal tool for assessing dental caries experience over a person's lifetime, necessitating that examiners of these epidemiological indices be properly standardized through a rigorous process such as calibration. The objective of the study was to develop a calibration process for diagnosing dental caries using the DMFT index among three groups of dentists. A cross-sectional study conducted with a population of 15 dentists who volunteered to participate, organized into 3 groups based on their area of practice. The calibration process was conducted both virtually and in-person. Statistical analysis involved calculating validity and reliability values using the Kappa coefficient, with a confidence level of 95% and significance set at p<0.05. For photographic results, Kappa values ranged from 0.55 (p<0.001) to 0.91 (p<0.001) in the first process, and from 0.73 (<0.001) to 1.00 (<0.001) in the second process. For dental assessments, values ranged from 0.20 (p=0.090) to 0.81 (p<0.001) in the first stage, and from 0.31 (p=0.002) to 0.89 (p<0.001) in the second. Out of the initial 15 examiners, 46.67% (n=7) achieved "almost perfect agreement" and 20.00% (n=3) achieved "substantial agreement."